2021
DOI: 10.3390/brainsci11020224
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Intervention Parameters of Endogenous Paired Associative Stimulation (ePAS)

Abstract: Advances in our understanding of neural plasticity have prompted the emergence of neuromodulatory interventions, which modulate corticomotor excitability (CME) and hold potential for accelerating stroke recovery. Endogenous paired associative stimulation (ePAS) involves the repeated pairing of a single pulse of peripheral electrical stimulation (PES) with endogenous movement-related cortical potentials (MRCPs), which are derived from electroencephalography. However, little is known about the optimal parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Three different cues were used to prompt the timing of voluntary movements. The standard visual cue (Figure 1a) has been described in previous studies [18,28] and was presented on a computer screen positioned approximately 1.2 m in front of the participant. This cue prompted participants to (i) bring their attention to the screen (2-3 seconds (s)); (ii) prepare for movement by watching a moving horizontal line (3 s); iii) execute the movement when the line ramps upwards (1.5 s); and then (iv) rest (6-8 s).…”
Section: Movement Cuesmentioning
confidence: 99%
“…Three different cues were used to prompt the timing of voluntary movements. The standard visual cue (Figure 1a) has been described in previous studies [18,28] and was presented on a computer screen positioned approximately 1.2 m in front of the participant. This cue prompted participants to (i) bring their attention to the screen (2-3 seconds (s)); (ii) prepare for movement by watching a moving horizontal line (3 s); iii) execute the movement when the line ramps upwards (1.5 s); and then (iv) rest (6-8 s).…”
Section: Movement Cuesmentioning
confidence: 99%
“…The electrical stimulation is timed to coincide precisely with the electroencephalography signal in the motor cortex to induce neural plasticity [46,47]. exciteBCI evolved from an endeavor to translate a neuromodulatory intervention that had been tested in healthy and stroke populations in a clinical research laboratory setting [46][47][48][49][50][51][52][53][54] into a rehabilitation device suitable for stroke rehabilitation. Prior feasibility work found that the neuromodulatory intervention, when delivered during simple ankle movements while seated, was not acceptable to people with stroke and was not feasible for rehabilitation [55].…”
Section: Introductionmentioning
confidence: 99%